A Systematic Review of Interventions to Promote Varied Social-Communication Behavior in Individuals With Autism Spectrum Disorder. Issue 6 (November 2019) - Wolfe, Katie; Pound, Sara; McCammon, Meka N.; Chezan, Laura C.; Drasgow, Erik
Individuals with autism spectrum disorder (ASD) may engage in repetitive social-communication behaviors that can limit their skill acquisition, access to reinforcement, and access to less restrictive settings. Basic and applied research indicates that variability, or the extent to which responses are topographically different from one another, is influenced by antecedent and consequence interventions. Our purpose in this study is to systematically review the literature on interventions to increase variable social-communication behaviors in individuals with ASD. We identified 32 studies through a database search and screened them using the What Works Clearinghouse (WWC) Single-Case Design Standards. Eighteen studies containing 55 cases met WWC Design Standards. We coded the descriptive characteristics and strength of evidence based on visual analysis from each of these 18 studies and calculated effect sizes using Tau-U. Our results indicate that most cases (65%) provide strong evidence of a functional relation between the interventions and varied social-communication behaviors, and the median Tau-U was .82. We discuss the implications of our results for practice and for future research on interventions designed to increase variability with this population.